Effect of food preparations on in vitro bioactivities and chemical components of fucus vesiculosus - André, Rebeca (2020)
Fucus vesiculosus is a brown macroalgae used in food and generally considered safe to be consumed, according to EU Directive (EC 258/97). The aim of this study is to analyze the e_ect of food preparation on F.vesiculosus of di_erent origins on what concerns its chemical constituents and final bioactivities. The aqueous extract of the seaweeds were obtained at di_erent temperatures, similar to food preparation and then purified by SPE. The compound identification was carried out by Liquid Chromatography High Resolution Mass Spectrometry (LC-HRMS/MS) and algae extracts microstructure were observed by Scanning Electron Microscopy (SEM). The activities were determined by using antioxidant activity, inhibition of acetylcholinesterase (AChE) and 3-hidroxi-3-methyl-glutaril-CoA (HMG-CoA) reductase (HMGR) together with Caco-2 cells line simulating the intestinal barrier. The activity of AChE and the HMGR were inhibited by the extracts giving IC50 values of 15.0 _ 0.1 _g/mL and 4.2 _ 0.1 _g/mL, respectively and 45% of the cholesterol permeation inhibition. The main compounds identified were phlorotannins and peptides derivatives. The mode of preparation significantly influenced the final bioactivities. Moreover, the in vitro results suggest that the preparation of F. vesiculosus as a soup could have hypercholesterolemia lowering effect.